Comedone-Like Lesions as a Manifestation of Lichen Planopilaris beyond the Scalp: A Case Report with Dermoscopic Features and Literature Review - Wimolsiri Iamsumang; Suthinee Rutnin; Poonkiat Suchonwanit (Karger Publishers, 2021)
Lichen planopilaris is a rare inflammatory condition that is also known as follicular lichen planus. Although the condition commonly affects the scalp, it sometimes involves the other regions of the body with a variety of clinical presentations. The involvement beyond the scalp is considered to be a generalized nature of disease process. In this report, we present a case of generalized follicular lichen planus in a 34-year-old Thai female presenting with comedone-like lesions on the trunk and extremities as well as scarring alopecia on the scalp. Dermoscopic features were also discussed.